2023
DOI: 10.17221/294/2022-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Sustainably produced butter: The effect of product knowledge, interest in sustainability, and consumer characteristics on purchase frequency

Abstract: Understanding buying behaviour for sustainable products is important for food producers and distributors. This study aims to examine the effect of knowledge of the product, interest in sustainability, and characteristics of consumers on the frequency of buying sustainably produced butter using the Stimulus-Organism-Response (SOR) model. In this study, two different types of butter were used, one produced by a well-known brand and the other by a less--known dairy. Data were collected through a structured online… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…So many scholars use the SOR model for causal analysis in the field of live-streaming e-commerce research. Jakubowska et al (2023) combined the SOR model to study the impact of consumer characteristics and product knowledge on consumer behavior when purchasing sustainable products [12]. Individual reactions as a necessary condition for behavior have received high attention.…”
Section: Theoretical Foundations and Hypothesis Development 21 Sor Th...mentioning
confidence: 99%
See 1 more Smart Citation
“…So many scholars use the SOR model for causal analysis in the field of live-streaming e-commerce research. Jakubowska et al (2023) combined the SOR model to study the impact of consumer characteristics and product knowledge on consumer behavior when purchasing sustainable products [12]. Individual reactions as a necessary condition for behavior have received high attention.…”
Section: Theoretical Foundations and Hypothesis Development 21 Sor Th...mentioning
confidence: 99%
“…Research has found that individuals who notice attractive faces are less likely to experience attentional shifts. Even if there is a transfer, there will be a path return and a re-browsing of the face hole, which greatly improves the fixation duration [12]. When consumers face a live streamer with an unattractive face, they are attracted to it to a lesser extent than an attractive-faced live streamer.…”
Section: Eye Tracking Technologymentioning
confidence: 99%
“…The observation of business operations in agricultural farms requires the management decision-makers to apply realistic management models in them in order to ensure the achievement of better economic production effects, as pointed out by authors such as (Hoyo et al, 2022;Jakubowska & Sadílek, 2023;Jordan et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…of heterogeneous decision-makers (Bakmaz et al, 2017;Duc et al, 2021;Arnautović et al, 2022;Jakubowska and Sadílek, 2023).…”
mentioning
confidence: 99%